Preexposure of Murine Macrophages to CpG Oligonucleotide Results in a Biphasic Tumor Necrosis Factor Alpha Response to Subsequent Lipopolysaccharide Challenge - Crabtree, Traves D. (American Society for Microbiology, 2001)
Bacterial DNA and synthetic oligonucleotides containing CpG sequences (CpG-DNA and CpG-ODN) provoke a proinflammatory cytokine response (tumor necrosis factor alpha [TNF-α], interleukin-12 [IL-12], and IL-6) and increased mortality in lipopolysaccharide (LPS)-challenged mice via a TNF-α-mediated mechanism. It was hypothesized that preexposure of macrophages to CpG-ODN would result in an increased TNF-α response to subsequent LPS challenge in vitro. Using the murine macrophage cell line RAW 264.7, we demonstrated both a rapid proinflammatory cytokine response (TNF-α) and a delayed inhibitory cytokine response (IL-10) with CpG-ODN. Preexposure of macrophages to CpG-ODN for brief periods (1 to 3 h) augmented TNF-α secretion and mRNA accumulation following subsequent LPS challenge (1 μg/ml). However, prolonged preexposure to CpG-ODN (6 to 9 h) resulted in suppression of the TNF-α protein and mRNA response to LPS. The addition of anti-IL-10 antibody to CpG-ODN during preexposure resulted in an increase in the LPS-induced TNF-α response over that induced by CpG-ODN preexposure alone. Thus, while brief preexposure of macrophages to CpG-ODN augments the proinflammatory cytokine response to subsequent LPS challenge, prolonged preexposure elicits IL-10 production, which inhibits the TNF-α response. Although the initial proinflammatory effects of CpG-DNA are well established, the immune response to CpG-DNA may also include autocrine or paracrine feedback mechanisms, leading to a complex interaction of proinflammatory and inhibitory cytokines.